Deformation and Sedimentary Responses to Top‐to‐North Shear Along the Range Front of the Big Bend of the Ailao Shan–Red River Shear Zone, SE Edge of the Tibetan Plateau, and Its Tectonic Implications. Issue 12 (24th November 2021) - Wang, E.; Fan, C.; Su, Z.
Abstract: Understanding the mountain–basin coupling relationship is fundamental to placing constraints on the tectonic evolution of the Ailao Shan mylonite shear zone, the key feature accommodating relative movement between the Tibetan Plateau and SE Asia, because a contemporary basin, namely Red River, bounds its middle segment on the northeast, along which the shear zone is bent from northwest–southeast to roughly east–west (The Big Bend). The basin comprises two units: the Mubang Breccia and the Lengdun Conglomerate of Early Oligocene and Late Oligocene–Early Miocene age, respectively. This study reveals evidence indicating that the Wubang Breccia marks a high‐strain zone, resulting from top‐to‐north shear (range‐front detachment (RFD), along which the mylonite on the footwall experienced northward bending in the form of creeping. Moreover, the Lengdun Conglomerate on the hanging wall was deposited as growth strata, overlying a thrust belt to the north. The latter marks the southern rim of the Yangtze block, composed of extensional fault blocks, whose northward displacement along the toe of the RFD was synchronized with the north–south extension across the Red River basin. The spatial and temporal relationships between the Red River basin and the Ailao Shan shear zone indicate that basin formation was controlled by the change in geometry of the shear zone. The Red River basin can be viewed as an extensional step‐over in the left‐lateral strike‐slip field, in which all sedimentary and deformation processes were controlled by the extension and subsequent topographic spreading, accommodated by the RFD. This indicates that the extensional crustal materials, including both Langdun Conglomerate and underlying extensional fault blocks, were all shed from the top of the Ailao Shan mylonite belt. The cause of bending of the shear zone is attributed to the northward movement of India with respect to South China and the bending process came to an end as the left‐lateral movement ceased. Plain Language Summary: The Ailao Shan‐Red River shear zone is bent from northwest‐southeast to east‐west along its middle segment, which is bounded by a linear intermountain basin on the northeast. The latter comprises two units: the Mubang Breccia and the Lengdun Conglomerate of Early Oligocene and Late Oligocene‐Early Miocene age. This study reveals evidence indicating that the Wubang Breccia marks a high‐strain zone, resulting from top‐to‐north shear (range‐front detachment [RFD]), along which the mylonite on the footwall experienced northward bending and the Lengdun Conglomerate on the hanging wall was deposited as growth strata, overlying a thrust belt to the north, which is composed of landslide blocks, whose northward displacement was accommodated by the toe of the RFD. The range front of the middle part of the shear zone can be viewed as an extensional step‐over in the left‐lateral strike‐slip field, in which all sedimentary and deformation processes are the manifestation of the gravitational collapse. This indicates that both the landslides and the Langdun Conglomerate were all shed from the top of the Ailao Shan. The cause of bending of the shear zone is attributed to the N‐S right‐lateral shear between India and South China. Key Points: The formation of the Red River basin is correlated with the change in geometry of the Ailao Shan‐Red River shear zone The range‐front top‐to‐north shear reflects the gravitational collapse of the Ailao Shan The change in geometry of the Ailao Shan‐Red River shear zone is caused by the N‐S right‐lateral shear between India and South China